Impact of outpatient SARS-CoV-2 infections in minority children. Issue 8 (26th February 2021) - Denny, Vanessa; Shah, Niva; Petro, Karolina; Choksey, Karishma; DeSantis, Elizabeth; Hintz, Molly; Rethi, Shruthi; Sanchez, Sarah; Sylla, Bernadette; Chiu, Stephanie; Gagliardo, Christina; Kairam, Neeraja; et al.
Abstract : Abstract: Data regarding COVID-19 in the adult population and hospitalized children is rapidly evolving, but little is known about children infected with severe acute respiratory syndrome coronavirus 2 who do not require hospitalization. In an observational, retrospective study we analyzed risk factors, demographics and clinical course of non-hospitalized patients ⩽ 21 years of age with COVID-19 infection. Of the 1, 796 patients evaluated, 170 were infected, and 40 participated in a telephone survey. Children older >10 years of age (OR: 2.19), Hispanic ethnicity (OR: 3) and residing in counties with higher rates of poverty (OR: 1.5) were associated with higher risk of infection, while older girls were more likely to experience prolonged duration of symptoms (median: 32 days). Consistent with prior reports, fever and cough were present in most of our patients. Shortness of breath, diarrhea, anosmia, and ageusia were more common in our outpatient population than previously reported. Larger studies addressing the clinical and psychosocial impact of CoVID-19 infection in children living in high-risk environments are warranted.